Workplace Realities for Intern Nurses: A Qualitative Study of Night Shift Challenges (IUBAT Review, 2026)
An internship serves as a bridge between academic and professional practice for nursing students. However, there is limited understanding about the challenges faced by intern nurses, particularly during the night shift. The primary objective is to explore the challenges faced by intern nurses during night shift duties and to identify areas of improvement. This is a qualitative phenomenological study in which strict statistical calculation were not followed rather data saturation guided the total sample size that is 10 in our case. Interns who had recently completed their internships at two government hospitals in Bangladesh participated in semi-structured in-depth interviews. The interviews were conducted in Bengali and later translated into English. Thematic analysis was conducted using Braun and Clarke’s six-phase framework. The study identified seven major challenges: sleep deprivation and lack of rest, heavy workload and staff shortage, limited food access, unsafe working conditions, limited support from senior staff, transportation difficulties, and emotional exhaustion. Participants also shared personal strategies for preparing for night shift and suggested several areas of improvement: designated resting areas, food access, enhanced security, and additional support from the senior nurses. Addressing these identified challenges is essential to improve the well-being of intern nurses and enhance clinical learning.IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 192-204